Analisis Pengaruh Brand Image, Brand Awareness, Corporate Social Responsibility Dan Segmentasi Pasar Pt. Xyz Terhadap Keputusan Pembelian - Leonard Marcell (Universitas Tarumanagara, 2019)
This study aims to analyze brand image, brand awareness, corporate social responsibility and market segmentation related to purchasing decisions on XYZ products. In this research data collection method used is online questionnaire and offline questionnaire to know the factors sought by customer in choosing product of XYZ. The sample is 130 respondents who consumed XYZ products. Data analysis method used is regression analysis. Based on the result of the research, the results shows that brand awareness, corporate social responsibility and market segmentation have positive and significant influence on purchasing decisions. Brand image has a positive but not significant toward purchasing decision.